2013
DOI: 10.1016/j.jmb.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Charge Pair Interactions in Transmembrane Helices and Turn Propensity of the Connecting Sequence Promote Helical Hairpin Insertion

Abstract: α-Helical hairpins, consisting of a pair of closely spaced transmembrane (TM) helices that are connected by a short interfacial turn, are the simplest structural motifs found in multi-spanning membrane proteins. In naturally occurring hairpins, the presence of polar residues is common and predicted to complicate membrane insertion. We postulate that the pre-packing process offsets any energetic cost of allocating polar and charged residues within the hydrophobic environment of biological membranes. Consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…1D, center). However, insertion of both HRs into the membrane should result in only G1 receiving a glycan, because, as previously demonstrated (33), G2 in these constructs was too close to the membrane to be efficiently glycosylated (Fig. 1D, left).…”
Section: Isolated Tmv Mp Hydrophobic Regions Are Not Inserted Into Bimentioning
confidence: 53%
See 1 more Smart Citation
“…1D, center). However, insertion of both HRs into the membrane should result in only G1 receiving a glycan, because, as previously demonstrated (33), G2 in these constructs was too close to the membrane to be efficiently glycosylated (Fig. 1D, left).…”
Section: Isolated Tmv Mp Hydrophobic Regions Are Not Inserted Into Bimentioning
confidence: 53%
“…Previous studies have shown that, in some cases, a neighboring TM helix can promote membrane insertion of a poorly hydrophobic TM region (30)(31)(32)(33). Therefore, we used the in vitro system to investigate the insertion of the two HRs connected by their native loop (residues 61 to 167, shown in gray) (Fig.…”
Section: Isolated Tmv Mp Hydrophobic Regions Are Not Inserted Into Bimentioning
confidence: 99%
“…Because of a lack of good assays, this idea has been difficult to test experimentally. The best support for it thus far has been obtained by end-point studies that compare the efficiency of membrane insertion of marginally hydrophobic transmembrane helices (TMHs) in their natural sequence context and when interacting residues in the protein have been removed by mutagenesis (8)(9)(10)(11)(12)(13), but such studies cannot identify the precise point during the translation-insertion-folding process when interactions between TMHs first develop.…”
mentioning
confidence: 99%
“…Helix-bundle membrane proteins display a large number of inter-helical contacts that are often formed between polar or even charged residues (25)(26)(27)(28). We noticed that some TM segments of GPCRs that are under study in our lab do not display favorable energies for full membrane insertion (29,30), an observation not unlike that reported for individual TMs of bacteriorhodopsin (31).…”
mentioning
confidence: 55%